Diplomatic relations between Iraq and Japan ( 1921- 1958) (Journal of the College of Basic Education, 2022)
Iraq's foreign policy during the monarchy era (1921-1958) was characterized by the establishment of a wide network of relations with Arab and foreign countries, including Japan, despite Britain's control over Iraq's foreign policy capabilities by virtue of the provisions of the British Mandate Regulations, as well as the provisions of the Iraqi-British Treaty. For the year 1930. All of this coincided, after Japan became the first economic power in the East since the first decade of the twentieth century, then entered the stage of colonial expansion, and took economic penetration in the countries of the Middle East, including Iraq, between 1921 and 1939, for